THE EFFICACY OF THERAPEUTIC MEASURES IN PATIENTS WITH GENERALIZED PERIODONTITIS ON THE BACKGROUND OF TYPE 1 DIABETES MELLITUS WITH CARDIOMYOPATHY ON SEPARATE PARAMETERS OF THE ORAL LIQUID - T. D. Zabolotnyj; O. I. Kordiyak; R. Y. Shkrebnyuk (Український стоматологічний альманах)
Abstract. This paper analyzes the efficacy of therapeutic measures in patients with generalized periodontitis and type I diabetes mellitus with cardiomyopathy for changes in the content of concentrations of endothelin-1 and nitrogen metabolites in the oral liquid as the result of use developed own scheme in the main group and control group, where treatment of dental diseases carried out by general accepted method. It is proved that in patients of the main group as a result of treatment were studied in a significant increase in the content of nitrogen metabolites on the background of reducing the concentration of endothelin-1 in the oral liquid compared to the data of control group.